Survival and Transcendence of Transnational Indigenous Latina Immigrants (ILIs) in the US - Margarita Machado-Casas (Sociedad Iberoamericana de Pedagogía Social, 2013)
Transnational indigenous Latino immigrants today seem to live multiple lives across multiple borders. Based on a 3-year Mix methods research study that took place in a new immigrant-receiving community in North Carolina, the manuscript describes the experiences of Indigenous Latina Immigrants (ILIs) living in the United States, specifically pedagogies of survival based on fluid social identities. The indigenous women who took part in this study had to adopt fluid unknown identities both in the home for cultural survival, and also outside the home (external identities) for physical and social survival, often in hostile environments. In addition, it raises questions about the ways multilingualism affects border mobility and transnationality as well as how indigenous Latina immigrants become Camaleónas guerreras (Chameleon Warriors) who use "critical survival tools" as a transnational bridge to facilitate their survival in a hostile US environment, the community, and in schools.